Global religions : an introduction - Juergensmeyer, Mark (Oxford University Press, 2003)
The essays collected here provide brief and accessible introductions to the major world religions in their global contexts. The volume begins with an introduction to the globalization of religion by Mark Juergensmeyer, and is followed by individual essays on Christianity, Islam, Judaism, Hinduism, Buddhism, and local religious societies. The book concludes with three essays reflecting on the global religious scene. Taken together, these essays provide a concise and authoritative introduction to the state of worldwide religion in the 21st century.